As estrambóticas aventuras de Cornélio Pires e a cultura caipira no cenário hegemônico da cultura brasileira - Andrade, Arlete Fonseca de (2012)
This research refers to the artistic and cultural production of Cornelius Pires (1884-1958) and the historical context of the country from the effects of colonization in the socio-economic and cultural, the presence of different ethnic groups and their inter-relations that have contributed to the formation of the regional culture paulista, the rustic. This background is relevant in the light of the stigmas attached to the rustics in view of "poverty" of São Paulo and its inhabitants by the end of the nineteenth century compared to other national locations and the downside of these distorted views with the resumption of popular culture on the part of intellectuals and artists by means of movements such as regionalism and the Modernism in search of a possible national identity. The justifications of these questions relate to historical tension that exists between popular culture and erudite culture and in the mediation of these two notions the contribution of laughter, humor as a way to smoothen the communication and insertion of the popular space in hegemonic society. Thus did Cornelius Pires, with his style facing the rural theme plus the humor in its production and penetrated hegemonic spaces allowing communication between the antagonisms present in our society such as: rural and urban, tradition and modernity, popular and erudite